2015
DOI: 10.1111/dar.12304
|View full text |Cite
|
Sign up to set email alerts
|

Are alcohol outlet densities strongly associated with alcohol‐related outcomes? A critical review of recent evidence

Abstract: The journal publishes both invited and unsolicited letters. LIQUOR LICENSING OR CONFOUNDING EVENTS? FURTHER QUESTIONS ABOUT THE INTERPRETATIONS OF MENÉNDEZ ET AL. (2015) Menéndez et al. [1] examined the cumulative effect of a series of licensing restrictions that took place in New South Wales in 2008. The results are extremely encouraging, estimating a 31.27% reduction in actual bodily harm (ABH) and a 39.70% reduction in grievous bodily harm (GBH). However, questions remain about the extent to which these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 84 publications
(161 reference statements)
3
122
0
1
Order By: Relevance
“…A recent systematic review (Gmel, Holmes, & Studer, 2015) examined 160 studies published between 2009 and 2014. While the authors found evidence of an association between alcohol outlet density and harm, they found little evidence of the causal direction and concluded that alcohol outlet density typically had little effect on individual-level alcohol use.…”
Section: Availability -Control System Outlet Density Days and Hoursmentioning
confidence: 99%
“…A recent systematic review (Gmel, Holmes, & Studer, 2015) examined 160 studies published between 2009 and 2014. While the authors found evidence of an association between alcohol outlet density and harm, they found little evidence of the causal direction and concluded that alcohol outlet density typically had little effect on individual-level alcohol use.…”
Section: Availability -Control System Outlet Density Days and Hoursmentioning
confidence: 99%
“…But some recent reviews have raised concerns about the generalisability and policy relevance of this evidence. For example, Gmel et al 10 note that the specific relationships between particular outlet types and particular types of harm vary substantially between studies, meaning the implications of changes to alcohol availability may be highly context-specific. In Australia and internationally, the trend for the past 40 years has been towards increasing the number of outlets, and minimising or abolishing limits on hours of the day and the week in which they are allowed to sell alcohol.…”
mentioning
confidence: 99%
“…In a recent systematic review, Gmel et al (2016) found evidence of an association between alcohol outlet density and harm but little evidence of causality, and concluded that alcohol outlet density had minimal effect on individual-level alcohol use. However, regarding accessibility, all our participants reported having supermarkets or corner shops, often several, close by, making it easy to buy alcohol, "too easy" as stated by one respondent.…”
Section: Discussionmentioning
confidence: 99%